Location Matters: Using Online Writing Tutorials to Enhance Knowledge Production - Luyt, Ilka (Discourse and Writing/Rédactologie)

(untitled) (Canadian Association for the Study of Discourse and Writing, 2022)
Students enrolled in asynchronous online courses explore much of the subject matter through computer-mediated discussion. In this context, students must often negotiate complex factors such as the course content, the assignment goals, their audience, disciplinary expectations, and the writing process. Writing Centres offer students support services to help them succeed in these text-heavy courses. Typically, students come to Writing Centres in person for help with their critical reading and writing assignments; however, increasingly, tutors are asked to participate in online settings to assist student learning. A question associated with online tutoring practices is whether students improve their writing skills when they are given the opportunity to get feedback from a tutor and from peers. How can a cooperative, collaborative pedagogical approach to computer-mediated tutoring support students and improve teaching? This paper examines a pedagogical exploration where one tutor interacted asynchronously with students by posting weekly writing activities. Students were asked to respond individually and collaboratively to each activity. I argue that when a tutor in an online course provides feedback, the collaboration creates a new online ecology of reflection and collaboration that may benefit students in their growth as writers. This exploration can be a useful writing pedagogy that can assist instructors by making stronger connections between students’ writing knowledge and writing practices.